Cuffed endotracheal tubes in neonates and infants of less than 3 kg body weight—A retrospective audit. Issue 5 (16th March 2021) - Zander, Désirée; Grass, Beate; Weiss, Markus; Buehler, Philipp K.; Schmitz, Achim
Abstract: Background: Large prospective clinical studies have shown that modern cuffed pediatric tracheal tubes can be used safely, even in children weighing ≥3 kg. There is a growing interest in their use in children weighing <3 kg so that they, too, can benefit from the potential advantages, particularly the high probability of these tubes fitting into and sealing the pediatric airway at the first intubation attempt. This study aimed to find a cut‐off body weight for procedures requiring a cuffed tracheal tube to seal the airway in children weighing <3 kg and to evaluate the frequency and predictive factors for the requirement to place a cuffed instead of an uncuffed tracheal tube. Methods: This study was a retrospective analysis of 269 children weighing 2000–2999 g, primarily intubated by pediatric anesthetists. Frequency of intubation with uncuffed Sheridan tubes versus cuffed Microcuff ® Pediatric Endotracheal Tube (PET) 3.0 mm ID was studied. Predictive variables were assessed by means of logistic regression analysis. The ROC curve for weight at intubation time and Youden index was calculated. Results: The 149 (55.4%) children were finally intubated with a cuffed tracheal tube. Logistic regression demonstrated that body weight at tracheal intubation and birth weight were the strongest predictors for the appropriateness of cuffed/uncuffed tracheal tubes. The threshold weight at tracheal intubation was 2700 g for a probability >50% of using a cuffed tracheal tube. Conclusion: Half of the children weighing 2000–2999 g received a Microcuff ® PET 3.0 mm ID, especially those with a body weight above 2700 g. Because of the anatomical dimensions in patients with a body weight of 2000–2999 g, cuffed tracheal tubes with smaller outer diameters may be required to better fit their airways.